2020
DOI: 10.1177/0284185120913000
|View full text |Cite
|
Sign up to set email alerts
|

Real-time dynamic 3-T MRI assessment of spine kinematics: a feasibility study utilizing three different fast pulse sequences

Abstract: Background Half-Fourier acquisition single-shot turbo spin-echo (HASTE), continuous radial gradient-echo (GRE), and True FISP allow real-time dynamic assessment of the spine. Purpose To evaluate the feasibility of adding dynamic sequences to routine spine magnetic resonance imaging (MRI) for assessment of spondylolisthesis. Material and Methods Retrospective review was performed of patients referred for dynamic MRI of the cervical or lumbar spine between January 2017 and 2018 who had flexion-extension radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Our dynamic images also had lower quality compared to the routine sequences although they were mainly diagnostic for the purpose of assessing listhesis or cord impingement in the cervical spine. In our experience, the 2D HASTE sequence produces better image quality when subjectively compared to other MRI techniques, including TrueFISP [8]. It may be that three very short sagittal sequences in maximum flexion, neutral, maximum extension may provide the same information with better resolution as compared to the CINE 2D HASTE, however one advantage of the dynamic sequence described herin is that the patient does not have to hold a given position, rather simply flex and extend as the sequence is acquired in real-time.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our dynamic images also had lower quality compared to the routine sequences although they were mainly diagnostic for the purpose of assessing listhesis or cord impingement in the cervical spine. In our experience, the 2D HASTE sequence produces better image quality when subjectively compared to other MRI techniques, including TrueFISP [8]. It may be that three very short sagittal sequences in maximum flexion, neutral, maximum extension may provide the same information with better resolution as compared to the CINE 2D HASTE, however one advantage of the dynamic sequence described herin is that the patient does not have to hold a given position, rather simply flex and extend as the sequence is acquired in real-time.…”
Section: Discussionmentioning
confidence: 77%
“…2D HASTE represents one of the oldest, most established and widely available sequences yet appears robust in the context of dynamic spine imaging. Indeed, the HASTE technique has been described in a range of dynamic clinical applications, yet with surprisingly little published with respect to kinematic imaging of the spine [8,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, ultrasonography showed a significantly higher diagnostic accordance rate for spina bifida, which could be attributed to its sensitivity to bones with strong high-echo signals. Although the true FISP sequence of fetal MRI could well image the spine, 17 the vertebrae with low signals seem indistinct among surrounding tissues. Interestingly, we encountered two cases of bony malformations during the study enrolment process.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of dynamic MRI in the musculoskeletal system is wide-ranging, from patellofemoral kinematics [1][2][3] to imaging of the hip in femoroacetabular impingement 4 and also dynamic spine imaging. 5,6 Especially when combined with thorough clinical evaluation, confirmation of abnormal joint kinematics by real-time MRI may be of considerable value in supporting therapeutic measures such as surgery or physical therapy. The video format of dynamic MRI is also ideal for advancing patient-centered care, improving patient literacy on their condition, and offering a potential catalyst for shared decision-making between surgeons and their patients.…”
Section: See Related Article On Page 1571mentioning
confidence: 99%